Special education faculty decision-making regarding designing and delivering family-professional partnership content and skills in the U.S. (September 2021) - Francis, Grace L.; Kilpatrick, Amy; Haines, Shana J.; Gershwin, Tracy; Kyzar, Kathleen B.; Hossain, Ishrath
Abstract: Despite policy and research supporting meaningful family-professional partnerships (FPPs) in U.S. schools, reported school practices demonstrate that such partnerships often do not come to fruition. One paramount barrier to FPP involves limited teacher preparation in university coursework. The purpose of this qualitative study was to explore special education faculty decision-making regarding designing and delivering FPP content and skills in U.S. institutions of higher education. The authors report three key themes: (a) FPP definitions and targeted skills, (b) rationale for prioritizing FPP skills, and (c) strategies for teaching FPP skills. Highlights: Family-professional partnership (FPP) was defined as educators and families working together to meet student needs. FPP skills participants targeted included communication, perspective-taking, self-awareness, and legally required skills. Personal and professional experiences and perceptions influenced FPP skills taught and emphasis placed on FPP in courses. Participants used case studies, parent interviews, and communication materials development to teach FPP skills.